PARASITE FAUNA IN VARIETIES OF THE ORNAMENTAL FISH CARASSIUS AURATUSAND DESCRIPTION OF THE BIOLOGICAL CYCLE OF ICHTHYOPHTHIRIUS MULTIFILIIS (CILIATEA ICHTHYOPHTHIRIIDAE), CAUSING MORTALITIES IN A HATCHERY FROM LIMA, PERU, 2007 - Gonzáles-Fernández, Julio G. (2012)
An amateur in Lima, Peru that deals with the breeding of varieties of the ornamental fish, Golden carp,(Carassius auratus), reported high occurrence of mortalities, 60%-70% of 2000 specimens in a few,days. Of these, 15 specimens (varieties of black telescope, oranda, red cap, lion's head and green coral),were selected in order to study and evaluate the gills and skin. Adult mobile spores and different,juvenile stages of Ichthyophthirius multifiliis "Ich", were found. The “disease of the white point” was,also observed in the presence of monogenean Gyrodactylus sp. and Dactylogyrus sp. Protozoans and,monogeneans were found to be the cause of mortality that also provoked an increase of mucus in the,gills as well as a strong detachment of the epidermis and the loss of,the caudal fin. Only one specimen,was found with hemorrhage in the bottom of the left eyeball. In order to control mortality, we applied,diluted formaldehyde, potassium permanganate and methylene blue. The best survival was obtained,with the formaldehyde treatment. In the Laboratory of Aquatic Biopathology of the Faculty of,Fisheries (UNALM), three specimens were placed in a fish tank with saline solution; Three days later,,the presence of large amounts of yellowish balls and numerous mobile young spores of the "Ich" were,observed on the surface of the aquarium. Furthermore, specimens of Zschokkella sp. were found in the,gallbladder; Thellohanellus sp. in both gills and internal structures. Hyphae of unidentified fungi were,also found inside the liver of some fishes. The parasites in C. auratus, the life cycle of I. multifiliis , its,histological alterations, and the success in treatment with formaldehyde are reported for the first time.